Therapeutic Management of Winter Coccidiosis in Cattle calves of Morigaon, Assam - Hazarika, A.; Das, M. (Indian Journal of Hill Farming, 2018)
Winter coccidiosis was observed in nine (9) non-descript cattle calves of about 4-10 months of age from Charaibahi village, Morigaon, Assam. Examination of fecal samples revealed presence of five species of Eimeria viz. E. bovis (88.88%), E. zuernii (66.66%), E. auburnensis (55.55%), E. ellipsoidalis (33.33%) and E. alabamensis (22.22%). Oocyst count per gram of feces ranged from 50 to 950 in infected calves. All the calves were treated successfully with Sulphadimidine @ 0.2g per kg b. wt. orally for 5 days, Paracetamol and Nimesulide @ 1 bolus per 100 kg b. wt. orally for 3 days and fluid therapy @ 500ml intravenously daily for 3 days. Multivitamin @ 250g per 100kg of feed was given daily as a supportive supplement for 1 month. After 5 days of treatment, the calves recovered gradually and started normal feeding.